Modification of activated carbon with titanium dioxide as a water treatment material - Fery Eko Pujiono; Tri Ana Mulyati; Mifta Nor Fizakia (AOSIS, 2019)
Activated carbon is a porous material that has high absorption power which can increase the quality of drinking water. Modifying the activated carbon with Titanium Dioxide (TiO2) can increase the quality of drinking water. This experiment study used activated carbon which then immersed in a Titanium Tetraisoproxide solution, each with a concentration of 5% and 10% with a ratio of 1: 5 then stirred with a magnetic stirrer for 2 hours. The results showed that FTIR peaks at a wavelength of 700-500 cm-1, as Ti-O. The diffractogram at 250, 400, 500, and 550 indicates anatase. The SEM-EDX results showed 79% carbon and there was a Ti of 4%. The Chemical Oxygen Demand (COD) test results showed that COD before being treated with ACTi was 1 ppm (pH = 6). After being processed with ACTi, the water has decreased COD levels of 93.28%, which is 0.0372 ppm (pH = 7). Modification of activated carbon with TiO2 has been carried out as evidenced by the characteristics of FTIR, XRD, and SEMEDX. Activated carbon modified with TiO2 can reduce COD levels by 93.28%.